Sex Specific Changes in Tryptophan Breakdown Over a 6 Week Treatment Period - Reininghaus, Eva Z.; Dalkner, Nina; Riedrich, Karin; Fuchs, Dietmar; Gostner, Johanna M.; Reininghaus, Bernd (Frontiers in Psychiatry, 2019)
Introduction. Despite the knowledge of sex differences concerning neurobiological parameters as well as clinical course of illness in individuals with mood disorders, the literature concerning tryptophan (Trp) breakdown, specific for women and men, is sparse to date. The current study aimed to evaluate sex differences in Trp, kynurenine (Kyn) and Kyn/Trp concentrations in general, as well as differences in changes of those concentrations over the course of a 6-week rehabilitation program in individuals with life-time unipolar affective disorder. For this purpose changes in Trp and Kyn as well as the Kyn/Trp concentrations between the time of admission (t1) and discharge (t2) were analyzed in dependence of sex. Furthermore, correlations between Trp and Kyn levels and clinical parameters were performed separately for male and female participants. Material and Methods. Results. For the current analysis 426 individuals with lifetime affective disorder completing a 6-week rehabilitation program were included. In both sexes, psychiatric symptoms decreased significantly over time. There was a significant difference between women (n=242) and men (n=184) regarding the changes in Trp, Kyn and Kyn/Trp over time even if controlled for relevant covariates (multivariate: F(3,369)=3.036, p=.029, η²= 0.024). Kyn as well as Kyn/Trp concentrations increased significantly in men over time (Kyn z=-2.077, p=.038; Kyn/Trp z=-2.307, p=021). Discussion. It is important to understand whether the Trp-Kyn pathway is generally activated or dysregulated in patients with affective disorders, or whether it perhaps differs between subsets of patients or between women and men. Such knowledge will be of particular relevance when selecting subjects for future treatment trials targeting the Trp-Kyn pathway. The main finding of the present study is the significant difference between women and men regarding the change in Trp, Kyn and Kyn/Trp over a 6-week psychiatric treatment period, when the depression severity scores as well as general psychiatric symptoms decreased. Sex specific changes in Trp-Kyn pathways have only been explored to a very small extent to date in the literature but are of high clinical relevance in the context of personalized medicine.